Religious Populism and Public Sphere in Indonesia - Robertus Wijanarko (Institut Teknologi Sepuluh Nopember, 2021)
Religious populism has strong and profound influence in Indonesia. It challenges the rational foundation of the democratic structure of the Indonesian Politics. This populist political movement utilizes religious language and symbols as their language of political articulation, negotiation, and contestation, which then occupies the real and virtual public sphere of the politics of Indonesia. Therefore, this use of religious language and symbols has placed democratic system in a serious risk. This critical study is intended to investigate the disadvantages of the use of religious language and symbols in the political arena in Indonesia. I will employ Paul Ricour’s thoughts in his writing, The Fragility of Political Language, as a lens of analysis for that phenomenon. Through that analysis I argue that the use of religious language and symbols in political discourse contradicts the provisional character of political language in democratic political settings. I suggest, therefore, the reenactment of the constitutional and rational foundation of democratic structure of Politics in Indonesia is seriously required.